1978
DOI: 10.4141/cjss78-003
|View full text |Cite
|
Sign up to set email alerts
|

Native Clay-Fixed Ammonium Content, and the Fixation of Added Ammonium of Some Soils of Eastern Canada

Abstract: '78. Native clay-fixed ammonium content, and the fixation of added ammonium of some soils of Eastem Canada. A study was made of the native clay-fixed NHa+ of some typical soils of Eastern Canada. Usually the amount of fixed NHa+ was related to the clay contents and increased down the profile but there were frequent exceptions to both of these generalizations. The amounts found ranged from l2to 450 p,g fixed NH++-N/g soil.In general, with some cultivated soils, the cropped areas had lower native fixed NHa+ con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
7
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 11 publications
4
7
0
Order By: Relevance
“…In experiments under laboratory conditions, Kowalenko and Cameron (1976) found that 50% of added NH 4 + was fixed within a short period of time, while in a field experiment, Kowalenko (1978) found that 59% of 152 kg N ha −1 added as (NH 4 ) 2 SO 4 was fixed within a few minutes after addition. In some soils of eastern Canada, more than 40% of the added NH 4 + was fixed in less than 2 h and further fixation was negligible (Sowden et al 1978). According to Chantigny et al (2004), the highest fixation of NH 4 + by clay minerals occurred within the first day and was greater in the clay soil (34% of applied 15 NH 4 -N) than in the sandy soil (11%).…”
Section: Influencing Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In experiments under laboratory conditions, Kowalenko and Cameron (1976) found that 50% of added NH 4 + was fixed within a short period of time, while in a field experiment, Kowalenko (1978) found that 59% of 152 kg N ha −1 added as (NH 4 ) 2 SO 4 was fixed within a few minutes after addition. In some soils of eastern Canada, more than 40% of the added NH 4 + was fixed in less than 2 h and further fixation was negligible (Sowden et al 1978). According to Chantigny et al (2004), the highest fixation of NH 4 + by clay minerals occurred within the first day and was greater in the clay soil (34% of applied 15 NH 4 -N) than in the sandy soil (11%).…”
Section: Influencing Factorsmentioning
confidence: 99%
“…The content of NH 4 + f and the capacity of soils to fix NH 4 + is related to parent material (Table 1), texture (Baethgen and Alley 1987), clay content (Opuwaribo and Odu 1974;Sowden et al 1978;Moyano and Gallardo 1988;Juang 1990), clay mineral composition (Feigin and Yaalon 1974;Sparks et al 1979;Doram and Evans 1983;Niederbudde 1983), the K concentration in soil solution, the degree of K saturation of the exchange complex of the soil colloids and . In some cases, the plough layer was thicker or shallower than 30 cm b Modified according to Scherer and Mengel (1979) c Modified according to Marzadori et al (1994) d Fraction <1…”
Section: Influencing Factorsmentioning
confidence: 99%
“…Soil Sci. 63: [631][632][633][634][635][636][637][638][639] (Aug. 1983) 63r incorporated into minerals during hydrolysis of the magma (Goldschmidt 1954), regional metamorphism of organic rich sediments (Martin et al 1970 (Stevenson 1959(Stevenson , 1962Schachtschabel 1961;Barker 1964;Vedder 1965 Sowden et al 1978), illite content (Feigin and Yaalon l9'74) and illite plus vermiculite content (Sparks et al 1979). Native fixed NH+* as generally measured in soils will also include NHo* that has been incorporated or fixed into minerals by pedological processes or by fertilizer application.…”
Section: 'Argile Dans Certains Sols Ontariens]mentioning
confidence: 99%
“…Mots cl6s: Fixation de l'ammonium, mise ir l'6quilibre, percolation sur colonnes, inhibition des enzymes microbiennes, concentration de l'extractif Ammonium fixed in the lattice of clays has been shown to occur in soils throughout the world (Young and Aldag 1982) and many places in Canada (Hinman 1964;Moore 1965;Sowden et al 1978). Clay fixation has been shown to influence the amount of ammonium that is in the soil solution and on cation exchange sites , and hence influenced the amount of nitrate released during laboratory incubations (van Schreven 1968; Cameron and Kowalenko 1976), under field fallow conditions (Kowalenko and Ross 1980), when immobilization was favored by carbon amendments (Kowalenko 1981) and in the presence of plant growth (Kowalenko and Cameron 1978;Preston 1982;Saha and Mukhopadhvav 1986: Wehrmann and Eschenhoff 1986; Scherer una W"mui l 993).…”
mentioning
confidence: 99%